Determination of T Follicular Helper Cell Fate by Dendritic Cells - Krishnaswamy, Jayendra Kumar; Alsén, Samuel; Yrlid, Ulf; Eisenbarth, Stephanie C.; Williams, Adam (Frontiers in Immunology, 2018)
T follicular helper (Tfh) cells are a specialized subset of CD4+ T cells that collaborate with B cells to promote and regulate humoral responses. Unlike other CD4+ effector lineages, Tfh cells require interactions with both dendritic cells (DCs) and B cells to complete their differentiation. While numerous studies have assessed the potential of different DC subsets to support Tfh priming, the conclusions of these studies depend heavily on the model and method of immunization used. We propose that the location of different DC subsets within the lymph node (LN) and their access to antigen determine their potency in Tfh priming. Finally, we provide a three-step model that accounts for the ability of multiple DC subsets and related lineages to support the Tfh differentiation program.